Fisika Fantastis: Guru-Guru Yang Membawa Sains Ke Kehidupan - Afini Alhamdani Essa; Raudatul Ardauyah (Lembaga Pengembangan Kinerja Dosen, 2023)
In our daily lives, we often find ourselves involved and reliant on scientific knowledge. This branch of knowledge encompasses not only the learning materials related to the theories and concepts of scientists but also includes attitudes and scientific products. Through the teaching of science, teachers can assist students in developing attitudes towards scientific learning through physics education, such as honesty, discipline, precision, objectivity, perseverance, and collaboration with others. Physics teachers play a role in instilling character values in students that need to be cultivated, including religiosity, multicultural spirit, respect for human individuals, justice, empathy for the poor, rational thinking, honesty, discipline, resilience, obedience to laws, and love for the homeland. This article will discuss how physics teachers educate students to have good character by applying science knowledge, attitudes, and products in life.